2023
DOI: 10.3389/fpls.2023.1137365
|View full text |Cite
|
Sign up to set email alerts
|

Shrub-mediated effects on soil nitrogen determines shrub-herbaceous interactions in drylands of the Tibetan Plateau

Abstract: IntroductionShrub promotes the survival, growth and reproduction of understory species by buffering the environmental extremes and improving limited resources (i.e., facilitation effect) in arid and semiarid regions. However, the importance of soil water and nutrient availability on shrub facilitation, and its trend along a drought gradient have been relatively less addressed in water-limited systems.MethodsWe investigated species richness, plant size, soil total nitrogen and dominant grass leaf δ13C within an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 83 publications
1
20
0
Order By: Relevance
“…Plant communities exhibit both positive and negative interactions between different plant species (Callaway and Walker, 1997). Cui et al (2023) confirmed that grasses exhibited a higher competitive ability compared to other functional groups, primarily attributed to their increased investment in roots and enhanced capacity for resource uptake.…”
Section: Response Of Leaf Traits To Climate Warmingmentioning
confidence: 85%
“…Plant communities exhibit both positive and negative interactions between different plant species (Callaway and Walker, 1997). Cui et al (2023) confirmed that grasses exhibited a higher competitive ability compared to other functional groups, primarily attributed to their increased investment in roots and enhanced capacity for resource uptake.…”
Section: Response Of Leaf Traits To Climate Warmingmentioning
confidence: 85%
“…It showed that facilitation and competition occur simultaneously, regardless of vegetation density. Facilitation processes are acting through the accumulation of soil nutrients (Cui et al, 2023;Grau et al, 2012) by maintaining suitable microclimatic conditions (Chen et al, 2020;Lyu et al, 2016) and by ameliorating physical conditions (Renard et al, 2016). Generally, any species found in a community experiencing stress could be facilitated (Liancourt & Dolezal, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Alpine ecosystem on the Tibetan Plateau has undergone rapid climate changes and intensity anthropogenic activities in recent decades (Kuang et al 2016), which are also associated with substantial structural and functional variations of alpine ecosystems, particularly the prevalently ecological process known as shrub encroachment (Wu et al, 2021;Zhao et al, 2023). In general, compared with herbaceous species, shrub species with greater aboveground and root biomass can provide more organic matter input soils (Zhou et al 2017;Cui et al, 2023) and enhance the accumulations of soil carbon and nitrogen (Li et al, 2019;Zhao et al, 2023). Shrub encroached into alpine grassland ecosystems can increase biodiversity, soil fertility, soil infiltration processes, ultimately attributing to strengthen ecosystem functioning (Butterfield et al, 2016;Cai et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the degree by which shrub encroachment caused variations in the ecosystem functioning could vary with the traits of encroaching shrubs (e.g., Leguminosae or Non-Leguminosae species). In semi-arid regions, Leguminosae shrubs can overcome drought stress and nutrients constraints to promote species richness, vegetation productivity, and carbon accumulation (Saixiyala et al, 2017;Ale et al, 2023). However, the encroachment of Leguminosae shrubs was differently associated with the ecosystem functioning than that of none-leguminous shrubs (Li et al, 2016;Zhao et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation